Sosialisasi Peranan Masyarakat Dalam Upaya Pencegahan Kekerasan Seksual Pada Anak di Desa Sekarwangi Kecamatan Cibadak Kabupaten Sukabumi - Srijadi , Yana Kusnadi (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
The aim of this Community Engagement Activity is to provide education on the importance of community involvement in social control as a preventive measure against child sexual abuse cases in Sekarwangi Village, Cibadak District, Sukabumi Regency. It serves as a form of community intervention involving public participation. The purpose of this activity is to offer insights into how community participation can contribute to social control in Sekarwangi Village and to provide recommendations involving individuals, families, social networks, organizations, and public policies for effective community intervention in the future.